2018
DOI: 10.1111/bjep.12262
|View full text |Cite
|
Sign up to set email alerts
|

The peer relations of pupils with special educational needs in mainstream primary schools: The importance of meaningful contact and interaction with peers

Abstract: Background and aims: Children with special educational needs (SEN) are generally less accepted by peers in school and have fewer friendships than those without SEN. However, little research has examined peer relations across multiple dimensions, relative to severity of need and in relation to classroom experiences and individual behavioural characteristics. This unique study aimed to extend understanding of the peer relations of pupils with differing levels of SEN support relative to children of differing atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…Research has shown that children with SEN and LD have difficulties in social skills (Freire et al, 2019;Wiener & Schneider, 2002). Compared to their classmates, children with SEN tend to have lower levels of prosocial behaviors (Dasioti & Kolaitis, 2018), are less accepted (Broomhead, 2019) and have fewer or no friends (Banks et al, 2018;Pinto et al, 2019). Also, students with LD present lower friendship quality, higher levels of conflict, more problems with relationship repair, and less stable relationships than their peers (Wiener & Schneider, 2002).…”
Section: School Adjustment In Children With Sen and Ldmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has shown that children with SEN and LD have difficulties in social skills (Freire et al, 2019;Wiener & Schneider, 2002). Compared to their classmates, children with SEN tend to have lower levels of prosocial behaviors (Dasioti & Kolaitis, 2018), are less accepted (Broomhead, 2019) and have fewer or no friends (Banks et al, 2018;Pinto et al, 2019). Also, students with LD present lower friendship quality, higher levels of conflict, more problems with relationship repair, and less stable relationships than their peers (Wiener & Schneider, 2002).…”
Section: School Adjustment In Children With Sen and Ldmentioning
confidence: 99%
“…Challenging aspects of school participation and inclusion of children with SEN and LD (Broomhead, 2019;Freire et al, 2019;Pinto et al, 2019) might expose these students as at risk of bullying. To the best of our knowledge, research on bullying in children with SEN and LD and its association with both the relationship with the teacher and students' social status in the peer group are scarce.…”
Section: Purpose Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Such factors include peer attitudes (de Boer et al, 2013), classroom norms (Gasser et al, 2017(Gasser et al, , 2018, and lack of teacher support (Mikami et al, 2013). From this perspective, it is important to provide opportunities for meaningful peer contacts (Grütter et al, 2018;Pinto et al, 2019). Moreover, teachers may need to address peer attitudes and friendships by creating inclusive classroom norms, modeling positive peer relationships, and giving children positive feedback (Mikami et al, 2013;Huber et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the same way, they show the relevance of different factors like the family context that acts positively when there is good communication between the members of the family [40] and/or the school context in which the cohesion of the class group influences the development of prosocial behaviours [41]. On the other hand, the study carried out by Pinto, Baines and Bakopoulou [42] determines that the development of contact between students with and without SEN favours the appearance of inclusive behaviours, so there could be a link between prosocial behaviours and this. However, there are no previous studies in which this relationship has been considered directly and from the perspective of students.…”
Section: Prosocial Behaviourmentioning
confidence: 82%